IMPLEMENTATION OF CUSTOMER RELATIONSHIP MANAGEMENT (CRM) IN MODERN MARKETING MANAGEMENT (LITERATURE REVIEW) - Permana, Herman; Tukiran, Martinus (Yayasan Education and Social Center, 2024)
This study discusses the implementation of Customer Relationship Management (CRM) in modern marketing management, focusing on the application of technology and its impact on the relationship between companies and customers. CRM is crucial in enhancing customer satisfaction, reinforcing loyalty, and facilitating personalization in marketing. Numerous studies in the past five years indicate that big data, artificial intelligence (AI), and cloud computing significantly enhance customer data collection and analysis, enabling companies to deliver more accurate and efficient services. However, the main challenge in implementing CRM is integrating various technology systems. Great opportunities lie in using data analysis to understand customer preferences and create more relevant and individual experiences. This study provides insights into how CRM can optimize marketing strategies in various sectors, including e-commerce, banking, retail, and B2B, and its impact on long-term customer relationships. With the right CRM, companies can create more value for customers and achieve greater success in marketing